An evolving paradigm for Africa and synthesis of the lessons from Asia - Diao, Xinshen; Silver, Jed; Takeshima, Hiroyuki; Zhang, Xiaobo (International Food Policy Research Institute, 2020)
Africa has experienced a paradigm shift in mechanization in the past three decades. The “new paradigm” has also given rise to new challenges and policy issues. By synthesizing the recent experiences in African and Asian countries, this chapter draws lessons from Asia and Africa under this new African paradigm. In doing so, the chapter first lays out the guiding theoretical framework used in 1987 by Pingali, Bigot, and Binswanger (PBB), based on the literature on farming systems evolution and induced technological change. The chapter then describes the “new paradigm,” which builds on PBB but also integrates the additional dimension of market failures associated, on the supply side, with custom hiring services, which have become the most common mode of mechanization among smallholders in developing countries. Applying this expanded framework, the chapter then reviews the Asian experience first. It highlights how mechanization has grown in the continent, having largely avoided supply-side market failures, thanks to several factors: smaller machine sizes;1 increased opportunities for multifunctional uses of machines; more secure land tenures that allow integration with formal credit markets; and the supportive, rather than distortive, nature of government subsidy policies. The chapter then turns to the experiences in Africa south of the Sahara (“Africa” hereafter) and highlights the emerging patterns of spatial variations in demand that are still largely consistent with the PBB framework. However, the chapter also stresses that market failures associated with custom hiring services on the supply side are substantial due to features unique to Africa, including the dominant types of large tractors, in addition to higher financial constraints on tractor ownership resulting from lack of secure land tenures and weak penetration of formal credit markets, as well as other barriers due to limited multifunctionality, lack of migratory services due to insufficient infrastructure and coordination failures, and insufficient technologies complementary to mechanization. Based on country experiences in Asia and Africa, the chapter also highlights key government policies that have not always been successful, including import restrictions (or removal thereof), inefficient technology and skill promotion, and insufficient provision of public goods. Last, given the country experiences and the identified appropriate roles of governments, the chapter concludes by describing the key lessons that are important for Africa’s mechanization pathway forward, including (1) understanding the emerging nature of demand, (2) actively promoting private hiring services, (3) eliminating or reducing distortions, and (4) prioritizing the mechanization technologies appropriate for African contexts.